Production of the bioactive plant‐derived triterpenoid morolic acid in engineered Saccharomyces cerevisiae. Issue 7 (8th May 2020) - Srisawat, Pisanee; Yasumoto, Shuhei; Fukushima, Ery O.; Robertlee, Jekson; Seki, Hikaru; Muranaka, Toshiya
Abstract: Morolic acid is a plant‐derived triterpenoid that possesses pharmacological properties such as cytotoxicity, as well as anti‐HIV, anti‐HSV, anti‐inflammatory, and antidiabetic effects. The significant therapeutic properties of morolic acid are desirable in the context of pharmacological and drug development research, but the low accessibility of morolic acid from natural resources limits its applications. In the present study, we developed a microbial system for the production of morolic acid. Using a combinatorial biosynthesis approach, a novel production pathway was constructed in Saccharomycescerevisiae by coexpressing BfOSC2 (germanicol synthase) from Bauhinia forficata and CYP716A49 (triterpene C‐28 oxidase) from Beta vulgaris . Moreover, we reconstructed the cellular galactose regulatory network by introducing a chimeric transcriptional activator (fusion of Gal4dbd.ER.VP16) to overdrive the genes under the control of the galactose promoter. We also overexpressed truncated HMG1, encoding feedback‐inhibition‐resistant form of 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase 1 and sterol‐regulating transcription factor upc2‐1, to increase the isoprenoid precursors in the mevalonate pathway. Using this yeast system, we achieved morolic acid production up to 20.7 ± 1.8 mg/L in batch culture. To our knowledge, this is the highest morolic acid titer reported from a heterologous host, indicating a promising approach for obtaining rare natural triterpenoids. Abstract : A yeast engineering that combines strategies to improve the production of plant‐derived triterpenoids. The combinatorial biosynthesis approach and reconstruction of the cellular galactose regulatory network to overdrive the genes under the control of the galactose promoter were implemented to produce rare natural triterpenoid, morolic acid. The demonstrated strategy may apply to many cases for the production of other specialized plant metabolites.